Dysregulation of arginine methylation in tumorigenesis - Li, Xiao; Song, Yaqiong; Mu, Weiwei; Hou, Xiaoli; Ba, Te; Ji, Shaoping (Frontiers in Molecular Biosciences, 2024)
Protein methylation, similar to DNA methylation, primarily involves posttranslational modification (PTM) targeting residues of nitrogen-containing side-chains and other residues. Protein arginine methylation, occurred on arginine residue, is mainly mediated by protein arginine methyltransferases (PRMTs), which are ubiquitously present in a multitude of organisms and are intricately involved in the regulation of numerous biological processes. Specifically, PRMTs are pivotal in the process of gene transcription regulation, and protein function modulation. Abnormal arginine methylation, particularly in histones, can induce dysregulation of gene expression, thereby leading to the development of cancer. The recent advancements in modification mediated by PRMTs and cancer research have had a profound impact on our understanding of the abnormal modification involved in carcinogenesis and progression. This review will provide a defined overview of these recent progression, with the aim of augmenting our knowledge on the role of PRMTs in progression and their potential application in cancer therapy.